Trauma, Identity, And The Collapse Of The American Dream: An Interdisciplinary Reading Of Philip Roth’s American Pastoral - Khayrulloeva Sitora Lutfulloevna (International Journal Of Literature And Languages, 2026)
According to recent advances in trauma theory, the Freudian approach of a sudden catastrophic event is challenged and, nowadays, trauma is viewed as a pluralistic, socially mediated process., Based on current research from the field of literary trauma studies, sociology, and moral psychology, this paper explores how Philip Roth’s American Pastoral (1997) turns the personal trauma of the individual into a societal crisis of cultural identity. The main theoritical framework for analysis are Judith Herman’s moral-psychological framework, Jeffrey Alexander’s sociology of cultural trauma, E. Ann Kaplan’s non-punctual trauma theory, and Michelle Balaev’s pluralistic model by which how familial, cultural, and narrative trauma are portrayed in the novel are explored. In the novel, trauma as a slow-burning system of repression with repercussions that go beyond the home to the national consciousness was depicted in the case of the Levov family. Symbolically, under the key scenes in the plot from Merry’s Levov’s stuttering, then bombing, to the challenges of Nathan Zuckerman’s narrative reconstruction, lay the main idea: “Swede” Levov’s “pastoral” myth is broken down because of the weight of its own ideals. This study incorporates contemporary interdisciplinary research on trauma, resilience, and cultural memory (Subica & Link 2021; Sonu et al. 2024; Bovey et al. 2025), and then, summarizes that in the example of American pastoral, the writer manages to establish a notion that trauma is not only a singular rupture, but also a relational process that connects the psyche, family, and nation.